Real-Time Implementation of Robust Loop-Shaping Controller for a VSC HVDC System - Faisal, Syed F.; Beig, Abdul R.; Thomas, Sunil (Energies (Basel), 2021)
Voltage source converter (VSC) based HVDC systems are one of the most promising technologies for high voltage bulk power transmission. The reliability and stability of a VSC-based HVDC system greatly depends on the design of a proper controller for the inner decoupled d-q current loop. One of the major causes of instability in a properly tuned controller is due to system parameter variation. This paper presents the design of a fixed parameter robust controller for the inner decoupled d-q current loop for a VSC-based HVDC system to deal with the uncertainties due to system parameter variations. The method of multiplicative uncertainty is employed in the robust design to model the variations in the system parameters. The robust control design was realized through a graphical procedure known as the loop-shaping technique. The graphical loop shaping technique is a much simpler and more straightforward method compared to the traditional H∞-based algorithms for robust controller design. The designed robust controller was experimentally verified using a real-time hardware in loop (HIL) system and was tested on a VSC HVDC system. The performance of the designed robust controller is compared to that of a traditional PI controller. It has been observed that a classical PI controller is effective for a given operating point, and its performance deteriorates when the operating point changes or when the system parameters change. The studies conducted using real-time hardware in the loop (HIL) system prove that the designed loop-shaping-based robust controller provides very good performance and stability for a wide range of system parameter variations, such as changes in resistance and the inductance of the VSC HVDC system compared to the PI controller tuned using conventional methods.